Invisible Writing: An Exploration of Attitudes towards Undergraduate Use of Standard Written English in UK Higher Education - Hill, Pat (Journal of Academic Writing, 2011)
Joan Turner (2004) suggests that for some students language only becomes ‘visible’ as a problem. With the expansion of UK higher education, more students will be discriminated against as their written language becomes visible. Recent scholarship recognises different literacies that students bring to higher education (Lea and Street 2000) and advocates moving away from a skills approach towards one which centres on how writers make meaning. This article endorses this positive progression from the ‘student deficit’ model but argues for an honest assessment of how students who do not already produce Standard Written English (Elbow 2000) can make their writing invisible so that readers are not distracted by ‘surface’ elements of the writing. Using empirical evidence and Pierre Bourdieu’s notion of ‘cultural capital’, it addresses a reluctance or inability to develop pedagogical solutions to a problem which is rooted in a persistently elitist and gate-keeping model of higher education.